2001
DOI: 10.1177/03079450094207
|View full text |Cite
|
Sign up to set email alerts
|

Salesperson Cooperation: The Influence of Relational, Task, Organizational, and Personal Factors

Abstract: Salesperson cooperation has become a crucial issue for the overall performance of most sales organizations. The authors examine the antecedents of task-specific, cooperative behaviors of salespersons toward other salespeople working in the same organization. The main theses of the study are that (1) the four major antecedent categories of factors—relational, task, organizational, and personal— constitute, collectively, the primary determinants of salesperson cooperation and (2) each antecedent category exerts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(168 citation statements)
references
References 112 publications
8
143
0
7
Order By: Relevance
“…Moreover, cooperation can be conditioned by culture and some cultures are more inclined to establish long-term relationships (Nohria and Eccles, 1992). Ylimaz and Hunt (2001) used transaction costs and game theory to explain cooperation based on providing greater benefits than costs. In fact, cooperation diminishes the need to assess risks such as economic pitfalls (Axelrod, 1984) and personal issues (Blau, 1964).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Moreover, cooperation can be conditioned by culture and some cultures are more inclined to establish long-term relationships (Nohria and Eccles, 1992). Ylimaz and Hunt (2001) used transaction costs and game theory to explain cooperation based on providing greater benefits than costs. In fact, cooperation diminishes the need to assess risks such as economic pitfalls (Axelrod, 1984) and personal issues (Blau, 1964).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Many studies have shown that trust leads to commitment (Becker, 1960;Axelrod, 1984;Morgan & Hunt, 1994;Wetzels et al, 1998;Garbarino & Johnson, 1999;Varamä ki, 2001;Ylimaz & Hunt, 2001;Ekelund, 2002;Rodriguez & Wilson, 2002;Wong & Sohal, 2002;Mukherjee & Nath, 2003). We propose that trust can be reinforced through interpersonal commitment (Morgan & Hunt, 1994) and ultimately enhance interorganizational commitment (Mavondo & Rodrigo, 2001).…”
Section: Trust (Tru)mentioning
confidence: 87%
“…To minimize these risks, firms in successful networks share resources and operations with others they can trust. Trust initially leads to greater interpersonal commitments (Becker, 1960;Axelrod, 1984;Morgan & Hunt, 1994;Wetzels et al, 1998;Garbarino & Johnson, 1999;Varamä ki, 2001;Ylimaz & Hunt, 2001;Ekelund, 2002;Rodriguez & Wilson, 2002;Wong & Sohal, 2002;Mukherjee & Nath, 2003) as does reciprocity (Kumar, Scheer & Steenkamp, 1995;Mavondo & Rodrigo, 2001). Moreover, interpersonal commitment ultimately influences interorganizational commitment (Yoon, Baker & Ko, 1994;Mavondo & Rodrigo, 2001).…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the extant literature (for an overview see Yilmaz and Hunt 2001) reveals that the antecedents of collaborative networks can be assigned to two different levels: First, scholars have examined individual-level determinants of collaborative behavior such as educational background (Hinds and Kiesler 1995); differences in race, sex, and citizenship (Chatman and Barsade 1995); cultural differences (Chen, Xiao-Ping, andMeindl 1998, Wagner 1995); organizational identification (Polzer 2004); identity confirmation (Milton and Westphal 2005); and individual predisposition to cooperate (Chatman andBarsade 1995, Deery andIverson 2005). Secondly, the effects of organizational variables have been investigated, e.g., physical distance between organizational members (Beersma, Hollenbeck, Humphrey, Moon, Conlon, and Ilgen 2003), procedural justice and open communication (Deery andIverson 2005, Kim andMauborgne 1998), communication technology (Hinds and Kiesler 1995), organizational climate (Iacobucci and Hopkins 1992), reward structures and sanction systems (Beersma, Hollenbeck, Humphrey, Moon, Conlon, and Ilgen 2003, Polzer 2004, Tenbrunsel and Messick 1999, as well as the size of the organization or work group respectively (Wagner 1995).…”
Section: Introductionmentioning
confidence: 99%